1983
DOI: 10.1093/infdis/147.4.676
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of DNA Sequences of BK Virus and JC Virus in Normal Human Tissues and in Diseased Tissues

Abstract: Available evidence suggests that BK virus (BKV) and JC virus (JCV) persist in the kidneys of healthy individuals after primary infection and may reactivate when the host's immune response is impaired. Data supporting this hypothesis are presented. A previous study had shown BKV to be present in the kidneys of eight (57%) of 14 subjects. In the present study, which extended the investigation to a total of 30 subjects, BKV DNA was found in the renal tissues of 10 (33%) subjects, and JCV DNA was found in the rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
293
0
7

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(303 citation statements)
references
References 31 publications
3
293
0
7
Order By: Relevance
“…In 1983, JCV DNA was detected in the kidneys of a PML patient by Southern blotting and in situ hybridization [25], predominately in medullar epithelial cells. That same year, 3 of 30 kidneys from non-PML patients were also shown to contain JCV DNA [72], implicating the kidneys as a site of latency. Another study demonstrated nonintegrated viral DNA in the spleen, lymph nodes, lungs, liver, and kidneys of three PML patients, supporting evidence for the hematogenous dissemination of JCV [73].…”
Section: Host Range Extended To Lymphocytesmentioning
confidence: 96%
“…In 1983, JCV DNA was detected in the kidneys of a PML patient by Southern blotting and in situ hybridization [25], predominately in medullar epithelial cells. That same year, 3 of 30 kidneys from non-PML patients were also shown to contain JCV DNA [72], implicating the kidneys as a site of latency. Another study demonstrated nonintegrated viral DNA in the spleen, lymph nodes, lungs, liver, and kidneys of three PML patients, supporting evidence for the hematogenous dissemination of JCV [73].…”
Section: Host Range Extended To Lymphocytesmentioning
confidence: 96%
“…Antibodies to BKV have been demonstrated in about 80% of normal adults (Dorries et al, 1994). Southern blots detected BKV DNA in 30% of cadaver kidneys from patients expiring from non-cancer causes, and, likewise, BKV DNA was detected in various tissues by PCR (Chesters et al, 1983;DeMattei et al, 1995). The signi®cance of SV40 in human tissues continues to be elucidated (Carbone et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…1 In generally clinically silent primary infection during childhood, BKV remains in a latent state, 2 mostly in the kidneys 3 and peripheral blood leukocytes. 4 Seroepidemiological studies have shown a 90% seroprevalence among adults worldwide.…”
Section: Introductionmentioning
confidence: 99%